2007
DOI: 10.1021/es071992c
|View full text |Cite
|
Sign up to set email alerts
|

Differential Uptake, Partitioning and Transfer of Cd and Zn in the Soil−Pea Plant−Aphid System

Abstract: The biomagnification of trace metals during transfer from contaminated soil to higher trophic levels may potentially result in the exposure of predatory arthropods to toxic concentrations of these elements. This study examined the transfer of Cd and Zn in a soil-plant-arthropod system grown in series of field plots that had received two annual applications of municipal biosolids with elevated levels of Cd and Zn. Results showed that biosolids amendmentsignificantly increased the concentration of Cd in the soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…None of the tested inocula caused a combined increase of the Cd and Zn uptake by willows. In agreement with our results, a preferable uptake of Zn compared to Cd was also observed in peas (Green and Tibbett 2008). Furthermore, in tomato, opposite changes in the Cd and Zn uptake were observed (Khan and Khan 1983), although these elements are supposed to behave similar in biological systems (Neibor and Richardson 1980).…”
Section: Discussionsupporting
confidence: 93%
“…None of the tested inocula caused a combined increase of the Cd and Zn uptake by willows. In agreement with our results, a preferable uptake of Zn compared to Cd was also observed in peas (Green and Tibbett 2008). Furthermore, in tomato, opposite changes in the Cd and Zn uptake were observed (Khan and Khan 1983), although these elements are supposed to behave similar in biological systems (Neibor and Richardson 1980).…”
Section: Discussionsupporting
confidence: 93%
“…This might suggest a physiological mechanism for exclusion of Cd from seed generating organs. Such an exclusion mechanism of Cd has been reported for other plant species (Harris and Taylor, 2001;Green and Tibbett, 2008). The relationships based on liable concentrations showed that the correlations between liable soil Cd and Cd in Ji-Dan mango fruits and between liable soil Pb and Pb in Tai-Nong mango fruits were at statistical significant levels (Fig.…”
Section: Relationships Between CD and Pb Concentrations In Orchard Sosupporting
confidence: 72%
“…Method blanks in each batch of samples were negligible. The transfer factors (TFs) of Cd and Pb from soil to fruit (edible part) were calculated using the following equation (Chojnacka et al, 2005;Li et al, 2006;Wang et al, 2006;Green and Tibbett, 2008;Williams et al, 2009):…”
Section: Methodsmentioning
confidence: 99%
“…As TF of Zn was less than 0.16, the transfer of Zn seemed to be somewhat inhibited from root to aerial parts in vegetables. This might be due to the antagonistic effect between Zn and Cd (Green and Tibbett 2008;Zheng et al 2007). The two elements possess similar chemical properties and may behave similarly in biological systems (Malik et al 2010).…”
Section: Translocation Of Heavy Metals In Plantsmentioning
confidence: 99%